MANAJEMEN STRATEGIK KEPALA SEKOLAH DI SMP ISLAM LOMBOK TENGAH NUSA TENGGARA BARAT - Zaenuddin, Zaenuddin; Citriadin, Yudin; Ismail, Ismail; Khalqi, Khairul (SOCIAL : Jurnal Inovasi Pendidikan IPS, 2025)
This study aims to analyze the implementation of strategic management by the principal of SMP Islam Islahul Ummah NW Lendang Kekah in improving educational quality. The study focuses on planning, organizing, implementing, and supervising curriculum, student affairs, facilities and infrastructure, and public relations. This study used a qualitative approach with a case study approach. Informants consisted of the principal, vice principal, and teachers. Data were collected through in-depth interviews. Data analysis was conducted through four simultaneous activity streams: data collection, data presentation, data condensation, and conclusions. Data validity testing consisted of four criteria: credibility, transferability, dependability, and confirmability. The results indicate that the principal applies visionary, participatory, consultative, and delegative leadership, enabling him to integrate the school's vision, mission, and goals into a focused work program. Curriculum development was carried out through school self-evaluation (EDS) with a SWOT analysis, curriculum document development, and monitoring and reflection. In student affairs, a variety of disciplinary programs, academic and extracurricular development, and Islamic character building are implemented. Facilities and infrastructure management focuses on inventory, procurement, repair, and arrangement of the school environment to support the learning process. Meanwhile, the public relations program plays a crucial role in building relationships with parents, committees, the community, and the government, as well as publicizing school achievements. Overall, the principal's strategic management implementation has created a conducive school climate, improved teacher and student quality, and strengthened the school's position in facing educational challenges. ABSTRAKPenelitian ini bertujuan untuk menganalisis implementasi manajemen strategik kepala SMP Islam Islahul Ummah NW Lendang Kekah dalam meningkatkan mutu pendidikan. Fokus kajian meliputi perencanaan, pengorganisasian, pelaksanaan, dan pengawasan di bidang kurikulum, kesiswaan, sarana-prasarana, dan hubungan masyarakat. Penelitian ini menggunakan pendekatan kualitatif dengan jenis penelitian studi kasus. Informan terdiri dari kepala sekolah, wakil kepala sekolah dan guru. Data penelitian dikumpulkan dengan wawancara mendalam. Analisis data dilakukan dengan empat alur kegiatan yang dilakukan secara bersamaan yaitu pengumpulan data, penyajian data, kondensasi data, dan kesimpulan. Pengujian keabsahan data terdiri dari empat kriteria yaitu kredibilitas, transferabilitas, dependabilitas, konfirmabilitas. Hasil penelitian menunjukkan bahwa kepala sekolah menerapkan kepemimpinan visioner, partisipatif, konsultatif, dan delegatif, sehingga mampu mengintegrasikan visi, misi, dan tujuan sekolah ke dalam program kerja yang terarah. Pengembangan kurikulum dilakukan melalui evaluasi diri sekolah (EDS) dengan analisis SWOT, penyusunan dokumen kurikulum, serta monitoring dan refleksi. Pada bidang kesiswaan, diterapkan program pendisiplinan, pembinaan akademik dan ekstrakurikuler yang bervariasi, serta penguatan karakter Islami. Pengelolaan sarana dan prasarana difokuskan pada inventarisasi, pengadaan, perbaikan, dan penataan lingkungan sekolah agar mendukung proses pembelajaran. Sementara itu, program humas berperan penting dalam membangun relasi dengan orang tua, komite, masyarakat, pemerintah, serta publikasi prestasi sekolah. Secara keseluruhan, implementasi manajemen strategik kepala sekolah mampu menciptakan iklim sekolah yang kondusif, meningkatkan kualitas guru dan siswa, serta memperkuat posisi sekolah dalam menghadapi tantangan pendidikan.